2021
DOI: 10.1002/ppul.25741
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of people with cystic fibrosis and frequent fungal infection

Abstract: Background: Individuals with cystic fibrosis (CF) and fungal airway infection may present with fungal bronchitis, allergic bronchopulmonary aspergillosis (ABPA) or may appear unaffected despite fungal detection. We sought to characterize people with CF with frequent detection of fungi from airway samples and determine clinical outcomes.Methods: This retrospective study included individuals with CF with ≥4 lower airway cultures over a 2-year baseline period and ≥2 years of follow-up. We defined two groups: ≤1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…As B. cenocepacia and other Bcc members have been increasingly observed in polymicrobial respiratory tract infections in CF patients [58,59], the ability of these organisms to use hydroxamate siderophores to pirate iron may provide B. cencocepacia with a similar advantage during infection, depending on the presence of co-infecting hydroxamate siderophore producers such as Achromobacter xylosoxidans (alcaligin), Aspergillus fumigatus and Aspergillus nidulans (TAF, ferricrocin, ferrichrome) and more rarely Bordetella bronchiseptica (alcaligin), Fusarium (TAF, ferricrocin), Penicillium (TAF, ferrichrome) and Rhodotorula (rhodotorulic acid) spp. [56,[60][61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…As B. cenocepacia and other Bcc members have been increasingly observed in polymicrobial respiratory tract infections in CF patients [58,59], the ability of these organisms to use hydroxamate siderophores to pirate iron may provide B. cencocepacia with a similar advantage during infection, depending on the presence of co-infecting hydroxamate siderophore producers such as Achromobacter xylosoxidans (alcaligin), Aspergillus fumigatus and Aspergillus nidulans (TAF, ferricrocin, ferrichrome) and more rarely Bordetella bronchiseptica (alcaligin), Fusarium (TAF, ferricrocin), Penicillium (TAF, ferrichrome) and Rhodotorula (rhodotorulic acid) spp. [56,[60][61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective, single-center study, our group compared clinical characteristics and outcomes in people with CF with frequent fungal positive cultures (most commonly Af) to those with no or rare fungi [ 58 ]. Individuals with frequent fungal positive cultures were more likely to have Stenotrophomonas maltophilia co-infection and Pseudomonas aeruginosa co-infection but were not more likely to have ABPA or lower lung function (culture positivity for Af is not a required criteria for a diagnosis of ABPA).…”
Section: Clinical Impact Of Af In Pwcfmentioning
confidence: 99%
“…When comparing those with rare fungal infection to those with frequent infection, there was no difference detected in lung function decline. Those with both ABPA and frequent fungal infection had a more clinically (but not statistically) significant decline in lung functions as well as a higher incidence of CF-related diabetes (CFRD) in comparison to those without ABPA and compared to those with ABPA but rare fungal positive cultures [ 58 ].…”
Section: Clinical Impact Of Af In Pwcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspergillus species (spp.) are the most common filamentous fungi in CF airways, with prevalence rates of up to 78% 2 . Moreover, Reece et al reported that Aspergillus fumigatus was likely more prevalent in early CF disease than was currently reported due to proving that molecular methods were superior in detecting A. fumigatus in pwCF sputum 3 .…”
Section: Introductionmentioning
confidence: 99%